Gouverner la biodiversité ou comment réussir à échouer - Devictor, Vincent (éditions Quae, 2021)
Why are we so successful in failing environmental policy? This book sheds light on the conditions of impossibility of governance of biodiversity. The author traces the role of the notion of biodiversity and conservation sciences in the ideological confrontation of the 1980s. Resource management becomes the watchword, sustainable development a rallying cry for peace, and nature a variable adjustment. It is the disappearance of the political content of the biodiversity crisis. He then explains how the biodiversity crisis is deprived of its ecological dimension. The living is considered by the politics of nature as a set of inert entities that lend themselves to sorting, cost-benefit analyzes or substitution. This double erasure, political and ecological, helps to forge the imagination of a global management of biodiversity. If the ecological challenge remains frozen in this double erasure, it can only succeed in failing. How to get out of this deadly and not very stimulating spiral? This book seeks to identify the points to be defended in order to reject this managerial model of the ecological crisis.